Characterization method for surface structure of amorphous carbon film
By depositing metal silver films on the surface of amorphous carbon films and using their surface Raman enhancement effect, the problem that it is difficult for the prior art to accurately obtain the most surface structure change information of amorphous carbon films is solved, and an accurate analysis of the nanothickness structure changes of the surface layer of amorphous carbon films is achieved.
Patent Information
- Application Number
- CN202510138271.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-11
AI Technical Summary
When analyzing amorphous carbon thin films, the analysis depth is usually at the submicron level, making it difficult to accurately obtain the changes in the most surface structure.
A metal silver film was deposited on the surface of the amorphous carbon film. The surface Raman enhancement effect of the metal silver film was used to obtain structural changes in the nanothickness of the amorphous carbon film surface through Raman spectroscopy.
This method can more accurately analyze the structural change information of the nanothickness of the surface layer of amorphous carbon thin film materials, broaden the application range of Raman spectroscopy, and help establish a more scientific structure-performance relationship of amorphous carbon thin film.
Smart Images

Figure CN119804418A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of analysis and detection, and in particular to a method for characterizing the surface structure of an amorphous carbon film. Background Art
[0002] Raman spectroscopy is a non-destructive characterization and analysis technology with the advantages of rich information, simple sample preparation, and low water interference. It is suitable for characterization and analysis of various forms of samples such as solutions, solids, gels and films. Raman spectroscopy is a scattering spectrum based on the Raman scattering effect discovered by Indian scientist Raman. It is generated by the interaction between light and chemical bonds in materials. It can provide information such as sample chemical structure, phase and morphology, crystallinity and molecular interaction. It is widely used in chemistry, materials, physics, biology, medicine, geology, environmental testing and other fields. Raman spectroscopy can be used to quickly confirm the type of material or distinguish different materials. At present, various Raman spectroscopy analysis techniques based on ultraviolet (244nm, 257nm, 325nm, etc.), visible (488nm, 514nm, 532nm, 633nm, etc.) and near-infrared (785nm, 980nm, 1064nm, etc.) wavelengths have been developed.
[0003] Amorphous carbon film is a type of surface protection material with carbon as the main component. It is widely used in aerospace, automobile, industrial manufacturing, optics, electronics and biomedical devices. As a fast and convenient characterization method, Raman spectroscopy has become an important detection tool for amorphous carbon films. In many applications, accurate understanding of the microstructural changes of amorphous carbon films is the basis for understanding the changes in their service performance. For example, for amorphous carbon films used in mechanical contact parts, the evolution of their surface structure is directly related to the application performance and reliability of the parts. However, as far as the most commonly used visible Raman spectroscopy is concerned, its analysis depth is usually at the submicron level, and the spectral information obtained is largely derived from the sub-surface structure, which interferes with the understanding of the changes in the most superficial structure. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for characterizing the surface structure of an amorphous carbon film. The characterization method provided by the present invention can accurately obtain the structural change information of the nanometer thickness of the surface layer of the amorphous carbon film.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for characterizing the surface structure of an amorphous carbon film, comprising the following steps:
[0007] Depositing a metallic silver film on the surface of the amorphous carbon film to be tested to obtain a composite film;
[0008] The composite film is subjected to Raman spectrum measurement to obtain the surface structure information of the amorphous carbon film; the metallic silver film surface of the composite film is the incident surface of the excitation light source of the Raman spectrum.
[0009] Preferably, the amorphous carbon film is a hydrogen-containing amorphous carbon film or a hydrogen-free amorphous carbon film.
[0010] Preferably, the thickness of the metallic silver film is 1.5-10 nm.
[0011] Preferably, the thickness of the metallic silver film is 3-5 nm.
[0012] Preferably, the metallic silver film is prepared by magnetron sputtering.
[0013] Preferably, the conditions of the magnetron sputtering include: using a metal silver target as the target material, using argon as the working gas, the working gas pressure is 0.08-0.5 Pa, the power of the target material is 0.5-1.5 kW, no bias is applied to the amorphous carbon film to be tested, and the sputtering time is 10-60 s.
[0014] Preferably, the target surface power density is 0.6-2.5 W / cm 2 .
[0015] Preferably, the excitation light source is a visible laser.
[0016] Preferably, the wavelength of the visible laser is 488 nm, 514 nm, 532 nm, 633 nm or 660 nm.
[0017] The present invention provides a method for characterizing the surface structure of an amorphous carbon film, comprising the following steps: depositing a metal silver film on the surface of an amorphous carbon film to be tested to obtain a composite film; performing Raman spectroscopy measurement on the composite film to obtain surface structural information of the amorphous carbon film. The present invention deposits a layer of metal silver film on the surface of a carbon film, and with the help of the surface Raman enhancement effect of metal silver, Raman spectroscopy can be used to obtain the structural information of the outermost layer of the amorphous carbon film. The present invention can broaden the scope of application of Raman spectroscopy, and can more accurately analyze the structural change information of the nanometer thickness of the surface layer of the amorphous carbon film material, which is helpful to establish a more scientific amorphous carbon film structure-performance relationship. Furthermore, the present invention can be characterized by commonly used visible Raman spectroscopy, without the need to use expensive short-wavelength ultraviolet laser sources, and is convenient and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A schematic diagram of the process of using Raman spectroscopy to characterize the nano-thickness structure of the surface layer of an amorphous carbon film in an embodiment;
[0019] Figure 2 The Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the single crystal silicon substrate in Comparative Example 1;
[0020] Figure 3 The Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the silicon substrate after the silver film is deposited in Example 1;
[0021] Figure 4 The Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the silicon substrate after the silver film is deposited in Example 2;
[0022] Figure 5 The Raman spectrum of the nanometer-thick hydrogen-free amorphous carbon film on the surface of the single-crystal silicon substrate in Comparative Example 2;
[0023] Figure 6 This is the Raman spectrum of the nanometer-thick hydrogen-free amorphous carbon film on the surface of the silicon substrate after the silver film is deposited in Example 3.
[0024] Figure 7 This is the Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the silicon substrate after the silver film was deposited in Comparative Example 3. DETAILED DESCRIPTION
[0025] The present invention provides a method for characterizing the surface structure of an amorphous carbon film, comprising the following steps:
[0026] Depositing a metallic silver film on the surface of the amorphous carbon film to be tested to obtain a composite film;
[0027] The composite film is subjected to Raman spectrum measurement to obtain the surface structure information of the amorphous carbon film; the metallic silver film surface of the composite film is the incident surface of the excitation light source of the Raman spectrum.
[0028] The invention deposits a metal silver film on the surface of an amorphous carbon film to be tested to obtain a composite film.
[0029] In the present invention, the amorphous carbon film contains a significant proportion of sp 3 The amorphous carbon film of hybridized carbon atoms can be a hydrogen-containing amorphous carbon film or a hydrogen-free amorphous carbon film. The present invention has no special requirements on the source of the amorphous carbon film, and it can be prepared by using commercial products or by a preparation method well known to those skilled in the art (such as preparation by chemical or physical vapor deposition). The present invention has no special requirements on the size of the amorphous carbon film, and it only needs to meet the measurement requirements of the Raman spectrometer. In the present invention, the surface of the amorphous carbon film is free of pollution.
[0030] In the present invention, the thickness of the metal silver film is preferably 1.5nm to 10nm, more preferably 3 to 5nm. The present invention controls the thickness of the metal silver film so that it has a significant Raman enhancement effect. If the thickness of the metal silver film is too large or too small, it will result in no enhancement effect or a greatly reduced enhancement effect. In the present invention, the metal silver film is preferably prepared by magnetron sputtering; the conditions of the magnetron sputtering preferably include: a metal silver target as the target material, argon as the working gas, a working gas pressure of 0.08 to 0.5Pa, preferably 0.1 to 0.3Pa, a target power of 0.5 to 1.5kW, preferably 1.0 to 1.5kW, no bias is applied to the amorphous carbon film to be tested, and the sputtering time is 10 to 60s, specifically based on meeting the thickness requirements of the metal silver film. In the present invention, the surface power density of the target material is preferably 0.6 to 2.5W / cm 2 , more preferably 1 to 2 W / cm 2 In the present invention, the specific operation of the magnetron sputtering is preferably: placing the amorphous carbon film to be tested in a magnetron sputtering coating chamber, and evacuating the coating chamber until the pressure is less than 5×10 -3 After reaching 0.08-0.5 Pa, argon gas is introduced into the coating chamber to maintain the gas pressure in the coating chamber at 0.08-0.5 Pa; then, the cathode power supply of the metal silver target is turned on, and the silver target is sputtered under the above power conditions to deposit a silver film on the surface of the amorphous carbon film to be tested.
[0031] The present invention sputters a silver target under low power conditions, which can make the metal silver film have a significant Raman enhancement effect. The present invention deposits an extremely thin metal silver film on the surface of the amorphous carbon film, utilizes the surface Raman enhancement effect of the silver film, and can use Raman spectroscopy to obtain the structural information of the outermost layer of the amorphous carbon film.
[0032] After obtaining the composite film, the present invention performs Raman spectrum measurement on the composite film to obtain surface structure information of the amorphous carbon film.
[0033] The present invention directly performs Raman spectrum measurement after depositing a metallic silver film on the surface of an amorphous carbon film without any further processing.
[0034] In the present invention, the surface of the metal silver film of the composite film is the incident surface of the excitation light source of the Raman spectrum, and the excitation light is preferably a visible laser, and the wavelength of the visible laser is preferably 488nm, 514nm, 532nm, 633nm or 660nm. The present invention has conducted experimental research on other conditions of the Raman spectrum, including laser power and number of scans, which have no effect on the characterization results. The present invention has no special requirements for the Raman spectrometer used for the Raman spectrum measurement. In an embodiment of the present invention, a laser confocal Raman spectrometer is used. The present invention does not impose special restrictions on the parameter setting of the Raman spectrum measurement, as long as the signal intensity required for the analysis is met. The present invention uses the commonly used visible Raman spectrum to obtain the structural information of the nanometer thickness of the surface layer of the amorphous carbon thin film material, such as the change in the hybrid structure of carbon atoms (sp 3 →sp 2 ), the present invention has no special requirements on the method of judging the structural change based on the Raman spectrum information obtained by Raman spectrum measurement, and the judgment can be made by using the common technical knowledge and conventional technical means of those skilled in the art.
[0035] The present invention provides a new method for characterizing amorphous carbon films based on commonly used visible Raman spectroscopy. Different from the traditional surface enhanced Raman spectroscopy technology of preparing the sample to be tested on the metal surface, the present invention deposits metal on the surface of the sample to be tested and enhances the Raman spectroscopy signal through the internal interface, thereby accurately obtaining the structural change information of the nanometer thickness of the surface layer of the amorphous carbon film.
[0036] In order to further illustrate the present invention, the characterization method of the surface structure of the amorphous carbon film provided by the present invention is described in detail below in combination with examples, but they should not be understood as limiting the protection scope of the present invention.
[0037] Taking hydrogen-containing and hydrogen-free amorphous carbon films prepared by chemical and physical vapor deposition methods as examples, the characterization method proposed in the present invention is verified and explained. The process of using Raman spectroscopy to characterize the nano-thickness structure of the surface layer of the amorphous carbon film in the embodiment of the present invention is as follows: Figure 1 shown.
[0038] Comparative Example 1
[0039] The preparation conditions of hydrogenated amorphous carbon film are as follows: chemical vapor deposition is used, acetylene is used as the source gas, the acetylene flow rate is 300 sccm, the deposition pressure is 1.4 Pa, a pulsed DC power supply is used, and discharge is performed under a voltage of -700 V to form a plasma, and a hydrogenated amorphous carbon film with a thickness of 90 nm is deposited on the surface of a single crystal silicon wafer.
[0040] The 90 nm thick hydrogenated amorphous carbon film on the surface of the silicon wafer prepared above was used as a sample to be tested, and Raman spectrum measurement was performed using a laser confocal Raman spectrometer with a wavelength of 532 nm.
[0041] Figure 2 This is the Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the single crystal silicon substrate in Comparative Example 1. It can be seen that it contains a strong single crystal silicon substrate signal.
[0042] Example 1
[0043] The 90 nm thick hydrogenated amorphous carbon film on the silicon wafer obtained in Comparative Example 1 was placed in a magnetron sputtering coating chamber and evacuated to a vacuum chamber pressure of less than 5×10 -3 After 150 sccm of argon was introduced into the coating chamber, the gas pressure was maintained at 0.1 Pa, and the silver target cathode power was turned on to sputter and deposit a silver film on the surface of the hydrogenated amorphous carbon film sample to be tested (no bias was applied to the hydrogenated amorphous carbon film). The silver target sputtering power was 1.0 kW (corresponding to a surface power density of about 1.4 W / cm 2 ), sputtering time 20s (the thickness of the silver film on the sample surface is 3nm).
[0044] After the silver film is sputtered and deposited, the vacuum chamber is inflated and the sample to be tested is taken out. A laser confocal Raman spectrometer with a wavelength of 532 nm is used, and the spectral test parameters exactly the same as those in Comparative Example 1 are adopted to directly perform Raman spectrum measurement on the sample surface where the silver film is deposited, and the Raman spectrum of the surface hydrogenated amorphous carbon film is obtained.
[0045] Figure 3 This is the Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the silicon substrate after the silver film is deposited in Example 1. It can be seen that the measured Raman spectrum only contains very weak Raman signals of the single-crystalline silicon substrate, indicating that this method can effectively obtain the surface structure information of the carbon film.
[0046] Example 2
[0047] The hydrogenated amorphous carbon film was prepared by the method of Comparative Example 1, and the silver film was sputtered and deposited on the surface of the hydrogenated amorphous carbon film according to the method of Example 1, except that the silver target sputtering power was 1.5 kW (corresponding to a surface power density of about 2.1 W / cm 2 ).
[0048] The Raman spectrum measurement was performed using the same test parameters as in Example 1 to obtain the Raman spectrum of the surface hydrogenated amorphous carbon film. Figure 4 This is the Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the silicon substrate after the silver film is deposited in Example 2. It can be seen that the measured Raman spectrum only contains very weak Raman signals of the single-crystalline silicon substrate, and mainly provides structural information of the surface hydrogenated amorphous carbon film.
[0049] Comparative Example 2
[0050] The preparation conditions of hydrogen-free amorphous carbon film are as follows: physical vapor deposition is used, Ar is used as process gas, deposition pressure is 0.1Pa, pulsed DC power supply is used, graphite target is sputtered under target current of 3.5A, and a 70nm thick hydrogen-free amorphous carbon film is deposited on the surface of single crystal silicon wafer.
[0051] The 70 nm thick hydrogen-free amorphous carbon film on the surface of the silicon wafer prepared above was used as the sample to be tested, and Raman spectrum measurement was performed using a laser confocal Raman spectrometer with a wavelength of 532 nm. The spectrum test parameters were the same as those in Example 1.
[0052] Figure 5 This is the Raman spectrum of the nanometer-thick hydrogen-free amorphous carbon film on the surface of the single-crystalline silicon substrate in Comparative Example 2. The spectrum contains a very strong single-crystalline silicon substrate signal.
[0053] Example 3
[0054] The method of Comparative Example 2 was adopted to prepare a hydrogen-free amorphous carbon film, and a silver film was sputtered and deposited on the surface of the hydrogen-free amorphous carbon film according to the method and conditions of Example 1.
[0055] The Raman spectrum measurement was performed using the same test parameters as in Example 1 to obtain the Raman spectrum of the surface hydrogen-free amorphous carbon film. Figure 6 This is the Raman spectrum of the nanometer-thick hydrogen-free amorphous carbon film on the surface of the silicon substrate after the silver film is deposited in Example 3. It can be seen that the measured Raman spectrum only contains a weak Raman signal of the single-crystalline silicon substrate, which is mainly the structural information of the nanometer-thick hydrogen-free amorphous carbon film on the surface.
[0056] Comparative Example 3
[0057] The 90 nm thick hydrogenated amorphous carbon film on the silicon wafer obtained in Comparative Example 1 was placed in a magnetron sputtering coating chamber and evacuated to a vacuum chamber pressure of less than 5×10 -3 After 150 sccm of argon was introduced into the coating chamber, the gas pressure was maintained at 0.1 Pa, and the silver target cathode power was turned on to sputter and deposit a silver film on the surface of the hydrogenated amorphous carbon film sample to be tested (no bias was applied to the hydrogenated amorphous carbon film). The silver target sputtering power was 2.0 kW (corresponding to a surface power density of approximately 2.8 W / cm 2 ), sputtering time 20s (the thickness of the silver film on the sample surface is 15nm).
[0058] After the silver film is sputtered and deposited, the vacuum chamber is inflated and the sample to be tested is taken out. A laser confocal Raman spectrometer with a wavelength of 532 nm is used to perform Raman spectrum measurement directly on the sample surface where the silver film is deposited, using the same spectrum test parameters as in Example 1.
[0059] Figure 7 This is the Raman spectrum of the nanometer-thick hydrogenated amorphous carbon film on the surface of the single crystal silicon substrate in Comparative Example 3. The spectrum contains a very strong single crystal silicon substrate signal.
[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for characterizing the surface structure of an amorphous carbon film, characterized in that: The following steps are involved: Depositing a metallic silver film on the surface of the amorphous carbon film to be tested to obtain a composite film; The composite film is subjected to Raman spectrum measurement to obtain the surface structure information of the amorphous carbon film; the metallic silver film surface of the composite film is the incident surface of the excitation light source of the Raman spectrum.
2. The characterization method according to claim 1, characterized in that The amorphous carbon film is a hydrogen-containing amorphous carbon film or a hydrogen-free amorphous carbon film.
3. The characterization method according to claim 1, characterized in that The thickness of the metallic silver film is 1.5-10 nm.
4. The characterization method according to claim 3, characterized in that: The thickness of the metallic silver film is 3-5 nm.
5. The characterization method according to claim 1, 3 or 4, characterized in that: The metal silver film is prepared by magnetron sputtering.
6. The characterization method according to claim 5, characterized in that The magnetron sputtering conditions include: using a metal silver target as a target material, using argon as a working gas, the working gas pressure is 0.08-0.5 Pa, the power of the target material is 0.5-1.5 kW, no bias is applied to the amorphous carbon film to be tested, and the sputtering time is 10-60 s.
7. The characterization method according to claim 6, characterized in that: The surface power density of the target material is 0.6 to 2.5 W / cm 2 .
8. The characterization method according to claim 1, characterized in that: The excitation light source is a visible laser.
9. The characterization method according to claim 8, characterized in that: The wavelength of the visible laser is 488 nm, 514 nm, 532 nm, 633 nm or 660 nm.
Citation Information
Patent Citations
Surface-enhanced Raman substrate based on diamond-like carbon film modified metal nano structure and preparation method thereof
CN101726480A
High-stability recyclable surface-enhanced Raman substrate and preparation method
CN104404512A
A method of depositing metal nanoparticles on a surface in an electrochemical process, the surface obtained by this method and its application
EP3382063A2
Flexible raman substrate and method for manufacturing the same
TWI611461B